Two vitalist critiques of Kantian ethical formalism - Gutiérrez, Eduardo Gutiérrez (Analysis. Journal of Philosophical Research, 2023)
This article analyzes Simmel and Ortega’s critiques of Kantian moral philosophy with two objectives: the first, to verify the vitalist core shared by both philosophers for their criticism of Kantian morality, in order to insert them within a tradition that starts with Schopenhauer and Nietzsche, without forgetting the importance of Hegelian criticism. The second, to highlight the receiving nature of said criticism; that is, to show that the criticism that Simmel and Ortega make of Kant is not a destructive criticism but a constructive one, based on a previous exercise of reception (“intradition of tradition”).